PROTECTIVE EFFECT OF SACCHARUM OFFICINARUM L. (SUGAR CANE) JUICE ON ISONIAZID INDUCED HEPATOTOXICITY IN MALE ALBINO MICE - Khan, Sadia Wazir; Tahir, Mohammad; Lone, Khalid Pervez; Munir, Bushra; Latif, Waqas (Journal of Ayub Medical College Abbottabad, 2015)
Background: Isoniazid (INH) is the drug of choice for treatment of tuberculosis (TB) and it is a well-known cause of acute clinical liver injury which can be severe and sometimes fatal. The study was designed to investigate the effects of Saccharum officinarum L. juice on oxidative liver injury due to INH in mice. Methods: This was a laboratory based experimental study. Thirty mice were divided into three groups, containing 10 mice each. Group A being the control; group B and C were experimental and were treated orally with INH 100 mg/kg per day and INH 100 mg/kg per day plus Saccharum officinarum L. juice 15 ml/ kg per day respectively for a period of 30 days. Blood samples were taken at 30th day by cardiac puncture under anaesthesia and liver in each was taken out for microscopic examination. Results: INH treated mice showed; rise in serum ALT, AST, ALP and total bilirubin levels (Mean±SEM), while group C mice treated with Saccharum officinarum L. juice significantly decreased the levels of these biochemical parameters. The histo-pathological examination of groups A showed normal liver structure which was deranged in (INH) group B, whereas group C showed significant recovery in histological structure. Saccharum officinarum L. constituents, especially flavanoids and anthocyanins have strong antioxidant properties which provides hepatoprotection against oxidative liver injury produced by INH. Conclusion: INH-induced liver injury is associated with oxidative stress, and co-administration of Saccharum officinarum L. juice (15 ml/Kg bw) may reduce this damage effectively in mice. Keywords: Isoniazid (INH), Saccharum officinarum, Hepatoprotection.